Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $f,g: S\to \mathbb{R}$. If we assume $f$ and $g$ are integrable over $S$, then I'm trying to show:

If $f$ and $g$ agree except on a set of measure zero, then $\int_S f=\int_S g$.

Also, how can we show:

If $f(x) \le g(x)$ for $x \in S$ and $\int_S f=\int_S g$, then $f$ and $g$ agree except on a set of measure zero.

share|improve this question
    
I prefer you to use $\TeX$ syntex for mathematical formula. First show that if $f \geq 0$ and $f$ vanishes a.e., then $\int f = 0$. This can be proved by monotone convergence theorem applied to $f_n = \min(f, n)$. Now if the positiveness is discarded, write $f = f^+ - f^-$. For the seonnd one, you may use the inequality $$ \int f \geq c \mu \{ f \geq c \}$$ where $c > 0$. This shows that $\mu \{ f \geq c \} = 0$ for all $c > 0$, hence $\mu \{ f > 0 \} = 0$. –  sos440 Feb 16 '12 at 7:56
add comment

1 Answer 1

up vote 2 down vote accepted

The first statement follows from the following fact: If $A$ is a set with measure zero, then $\int_A f\,dm=0$ for any measurable function $f$. Now, if $f=g$ on $S-A$ where $A$ is a set with measure zero, then we have $$\int_S f\,dm=\int_{S-A}f\,dm+\int_{A}f\,dm=\int_{S-A}f\,dm=\int_{S-A}g\,dm=\int_{S-A}g\,dm+\int_{A}g\,dm=\int_S g\,dm.$$

For the second statement, if $f\geq g$, then $f-g\geq 0$. For $\epsilon>0$, let $S(\epsilon)=\{x | f(x)-g(x)\geq \epsilon\}$ which is a measurable set. Then we have $$\tag{1}\int_{S(\epsilon)}(f-g)\geq\epsilon\,m(S(\epsilon)).$$ By assumption, we have $$\tag{2}0=\int_{S}(f-g)dm=\int_{S-S(\epsilon)}(f-g)dm+\int_{S(\epsilon)}(f-g)dm\geq \int_{S(\epsilon)}(f-g)dm$$ since $f-g\geq 0$ on $S$. Combining $(1)$ and $(2)$, we have $$m(S(\epsilon))=0\mbox{ for all }\epsilon>0.$$ Note that $$\{x\in S| f(x)\neq g(x)\}=\{x\in S| f(x)>g(x)\}=\bigcup_{n=1}^\infty S(\frac{1}{n}).$$ This implies that $\{x\in S| f(x)\neq g(x)\}$ has measure zero.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.